Recent developments in our understanding of the physiological role of PP-fold peptide receptor subtypes - Berglund, Magnus M; Hipskind, Philip A; Gehlert, Donald R (Experimental biology and medicine (Maywood, N.J.), 2003)
The three peptides pancreatic polypeptide (PP), peptide YY (PYY), and neuropeptide Y (NPY) share a similar structure known as the PP-fold. There are four known human G-protein coupled receptors for the PP-fold peptides, namely Y1, Y2, Y4, and Y5, each of them being able to bind at least two of the three endogenous ligands. All three peptides are found in the circulation acting as hormones. Although NPY is only released from neurons, PYY and PP are primarily found in endocrine cells in the gut, where they exert such effects as inhibition of gall bladder secretion, gut motility, and pancreatic secretion. However, when PYY is administered in an experimental setting to animals, cloned receptors, or tissue preparations, it can mimic the effects of NPY in essentially all studies, making it difficult to study the effects of PP-fold peptides and to delineate what receptor and peptide accounts for a particular effect. Initial studies with transgenic animals confirmed the well-established action of NPY on metabolism, food-intake, vascular systems, memory, mood, neuronal excitability, and reproduction. More recently, using transgenic techniques and novel antagonists for the Y1, Y2, and Y5 receptors, NPY has been found to be a key player in the regulation of ethanol consumption and neuronal development.